Strategi Digitalisasi Teknologi dalam Pemasaran Bank Syariah : Studi Kasus pada PT. Bank Muamalat Probolinggo - Pertiwi, Fia Ayuning (CV. Ulil Albab Corp, 2024)
The muamalat bank branch office in Probolinggo has introduced various digital financial technology-based service, such as virtual account, M-Banking (M-DIN) and ATMs to meet the needs of customers in managing financial transactions. The purpose of this research is to identify competitive marketing strategies in Muamalat banking. This qualitative field research employs interviews and documentation to obtain data. The primary data source is interviews with muamalat bank leaders, while secondary sources are drawn from written works or other types of documentation to complement primary data. Based on the research findings, muamalat bank branch office in Probolinggo rewuires sustained introduction steps to enhance the effective and efficient use of the systems, as there are still customers unfamiliar with muamalat fintech digital services.